Environmental Protection in The Urban Layout - Uteniazova Naubakhar Amanbayevna (Zien Journals, 2022)
The urgency of the problem of the environment in most developing areas was the reason for the development in each scheme and in each project of urban, regional planning of a special section "Environmental Protection"
Keywords: Ecology; urban planning; state; territory